Anthropogenic activities and the introduction of exotic species negatively impact the lotic ecosystem of the Trici River (Tauá, Ceará) - Lima, Silvio César Gomes de; Andrade, José Eduardo de (Seven Editora, 2024)
The city of Tauá, in the region of Inhamuns (about 350 kilometers from the capital Fortaleza), with a population of 54,271 inhabitants (Demographic census carried out in 2007). The city of Tauá is part of the municipality of Tauá, which has an area of 6,390 km² with a population of 230,538 inhabitants. The presence of vegetation in the lotic ecosystems of the Trici River and the lentic ecosystems of the Parque da Cidade lagoon, which are part of the natural landscape of the Inhamuns region, is conspicuous. However, for decades it has become evident that anthropogenic activities (raw sewage; uncontrolled burning; territorial expansion of neighborhoods; dumping of non-recyclable garbage, among other situations) are increasingly present in ecosystems, particularly in the lotic ecosystem of the Trici River, which runs through the city of Tauá. The objective of the present work was to carry out an initial study on the environmental threats, usually anthropogenic in nature, in the lotic ecosystem of the Trici River in a scenario of global warming and local drought. The preliminary results of the present study incontestably demonstrate that the lotic ecosystem of the Trici River presents numerous modifications of an anthropogenic nature, such as: pollution by garbage of all kinds; depredation and reduction of its banks; introduction of alien species to the ecosystem. Strong measures in the aspect of research and environmental education must be implemented urgently. DOI:https://doi.org/10.56238/sevened2024.010-027